Hubungan antara kadar hepcidin dan kadar soluble transferrin receptor pada •-thalassemia trait - Anitawati dr; Adi Koesoema Aman; Ratna Akbari Ganie (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction : Hepcidin plays important role in regulating ferrum circulation and ferrum toxicity in thalassemia patient. Soluble transferrin receptor(sTfR) is an ineffective eritropoetic measurement parameter which is more accurate. To find out correlation between Hepcidin and sTfR in •-thalassemia trait patientMethods : This is a cross sectional study which conducted on 28 patient with•-thalassemia trait who consulting in RSUP Haji Adam Malik Medan in March-May 2016. Analysis included full blood count, electrophoresis Hb, Hepcidin,and sTfR serum. Results : There was correlation between Hepcidin and sTfR serum level in •--thalassemia trait patient, this study showed strong correlation (r= 0.613). Statistical analysis found significant correlation between Hepcidin and sTfR level ( p = 0.001). Conclusion : This study showed strong correlation between Hepcidin and sTfR level in •-thalassemia trait patient. Keywords : •-thalassemia trait, Hepcidin, sTfR